Effect of harvesting time on groundnut yield and yield components in Northern Mozambique - Jnr, Emmanuel Zuza; Muitia, Amade; Amane, Manuel I V; Brandenburg, Rick L; Mondjana, Ana M (Journal of Postharvest Technology, 2018)
Groundnut (Arachis hypogaea L.) is one of the most important legume crop in Mozambique which is grown for food as well as cash. It’s an indeterminate growth habit and below the ground nature of fruiting makes it difficult to determine the time of optimal maturity of pods. This results in reduced crop yields if either harvested too early or too late. The objectives of the study were therefore to evaluate the effect of harvesting time for optimum yield of groundnut pods for three Spanish varieties and to estimate yield losses as a result of harvesting time at two locations, namely; Nampula Research Station (PAN) and Mapupulo Agricultural Research Center (CIAM) in Nampula and Cabo Delgado provinces respectively. The experiment was laid out in a randomized complete block design in a split-plot arrangement with four replicates. The varieties (ICGV-SM-99568, ICGV-SM-01514 and JL-24) were the main factor and three harvesting times (10 days before physiological maturity, at physiological maturity and 10 days after physiological maturity) were the sub-plots. Highest pod yields of 1276.9 and 1503.6 kg/ha were recorded at CIAM and PAN as a result of harvesting at physiological maturity compared to harvesting 10 days before (904.6 and 950 kg/ha) and 10 days after (826.8 and 1047.4 kg/ha) physiological maturity. Furthermore, yield losses ranged from (16-25 %) and (30-40 %) as a result of harvesting groundnut 10 days before and 10 days after physiological maturity respectively. It is therefore advisable that farmers’ harvest their groundnut crop at physiological maturity in order to obtain maximum pod yields of the groundnut.